INES – An Interface Between Experiments and Simulation to Support the Development of Robust Process Designs. Issue 12 (3rd November 2015) - Asprion, Norbert; Benfer, Regina; Blagov, Sergej; Böttcher, Roger; Bortz, Michael; Berezhnyi, Maksym; Burger, Jakob; Harbou, Erik von; Küfer, Karl‐Heinz; Hasse, Hans
Abstract: The development of chemical processes is based on both experiments and process simulations. Data evaluation and reconciliation, model development and validation, and design of experiments are essential steps in this procedure. The different tools and approaches available are usually not supported in an integrated way in the process developer's workflow. Therefore, a framework for process design was created and integrated in a tool box which supports process design comprehensively. It contains methods for data selection and reconciliation, sensitivity analysis, model validation and model adjustment. Abstract : Methods supporting the process designer are implemented into industrial workflow: Especially selection of operating points for model validation and adjustment is facilitated. Sensitivity analysis is used to investigate impact of parameters on objectives and is implemented within multi‐criteria optimization for robust process design.